Brain energy metabolism and intracranial pressure in idiopathic adult hydrocephalus syndrome - Agren-Wilsson, A (BMJ Group, 2005)
Background: The symptoms in idiopathic adult hydrocephalus syndrome (IAHS) are consistent with pathology involving the periventricular white matter, presumably reflecting ischaemia and CSF hydrodynamic disturbance. Objective: To investigate whether a change in intracranial pressure (ICP) can affect energy metabolism in deep white matter. Methods: A microdialysis catheter, a brain tissue oxygen tension probe, and an ICP transducer were inserted into the periventricular white matter 0–7 mm from the right frontal horn in 10 patients with IAHS. ICP and intracerebral PtiO(2) were recorded continuously during lumbar CSF constant pressure infusion test. ICP was raised to pressure levels of 35 and 45 mm Hg for 10 minutes each, after which CSF drainage was undertaken. Microdialysis samples were collected every three minutes and analysed for glucose, lactate, pyruvate, and glutamate. Results: When raising the ICP, a reversible drop in the extracellular concentrations of glucose, lactate, and pyruvate was found. Comparing the values during baseline to values at the highest pressure level, the fall in glucose, lactate, and pyruvate was significant (p<0.05, Wilcoxon sign rank). There was no change in glutamate or the lactate to pyruvate ratio during ICP elevation. PtiO(2) did not decrease during ICP elevation, but was significantly increased following CSF drainage. Conclusions: Raising intracranial pressure induces an immediate and reversible change in energy metabolism in periventricular white matter, without any sign of ischaemia. Theoretically, frequent ICP peaks (B waves) over a long period could eventually cause persisting axonal disturbance and subsequently the symptoms noted in IAHS.